"Convince Your Patients and You Will Convince Society": Career Decisions and Professional Identity Among Nurses in India. (March 2018) - Johnson, Sonali E.
This article reports on the results of qualitative research to investigate the career plans of Indian nurses working in the southern Indian city of Bangalore. The globalized health care market in Bangalore has generated opportunities for an increasingly diversifying profession, many of whose members are keen to pursue global careers, work in specialized clinical settings, and pursue further education, and whose sense of professional identity is strongly influenced by these career choices. The research drew upon interviews with 56 nurses employed across six sites, including public and private health facilities. Decision-making related to the setting of nursing work and the negotiation of boundaries between medical "treatment" were of analytical interest in understanding career drivers and the professional identity of nurses working predominantly in the context of hospital care. Lateral trajectories were found to be important to the construction of a career in nursing—where the extent to which nurses could demonstrate competencies in clinical skill and knowledge and maintain professional control over the practice of nursing are key aspects in constructing a career. The renegotiation of nursing's public image is at the heart of professionalizing strategies being adopted by nursing's leaders and is also evident in the accounts presented by hospital nurses in their depictions of nursing practice and career plans. The findings suggest that greater attention to the professional project of nursing in India and the construction of nursing careers would benefit the development of more responsive human resource policies around the retention of nurses.